Effect of tillage and method of sowing on performance of greengram (Vigna radiata) varieties during summer and rainy seasons - DODWADIYA, K S; SHARMA, A R (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted at New Delhi during summer and rainy seasons of 2006 to evaluate the effect of tillage practices (conventional and zero) and method of sowing (flat and raised-bed) on five greenngram varieties, viz Pusa Baisakhi, PS 16, Pusa 9531, Pusa Vishal and SML 668. Mean seed yield of greengram remained unaffected due to tillage practices in summer season, but zero tillage caused a drastic reduction in yield in the rainy season. Bed-planted crops gave the same yield, despite higher stover production. SML 668 gave the highest seed yield in both seasons, followed by Pusa Vishal and Pusa 9531. Zero tillage was more profitable in summer, while conventional tillage was the best practice in the rainy season. It is recommended to grow newly-released variety SML 668 during summer as well as rainy season for higher productivity and profitability. The additional seed yield and monetary benefits with raised-bed sowing were not large, but the expected savings in irrigation water and other inputs might improve the profitability of this practice over flat sowing.